Enhanced glucose production in norepinephrine and palmitate stimulated hepatocytes following endurance training - Sumida, Ken D.; Lordan, Vera M.; Donovan, Casey M. (Frontiers in Physiology, 2024)
Enhanced hepatic gluconeogenesis plays an important role in exercise glucose homeostasis when hepatic glycogen stores are depleted. Livers from trained animals demonstrate greater rates of gluconeogenesis in the presence of elevated substrate with and without hormonal stimulation. Training has been reported to have a particularly profound impact on norepinephrine-stimulated gluconeogenesis, but this was only demonstrated in the presence of other gluconeogenic hormones. Here we reexamine the impact of endurance training on norepinephrine-stimulated gluconeogenesis in the absence of any other hormones. Isolated hepatocytes from trained and untrained rats were incubated in 6 mM lactate with various concentrations of norepinephrine (0 nM–20 nM). Absent norepinephrine, gluconeogenic rates were significantly greater from trained hepatocytes compared to controls (97.2 ± 6.7 vs 57.6 ± 8.7 nmol/mg protein; p < 0.01). In the presence of NE (0.5–20 nM), gluconeogenesis from trained liver cells was significantly greater at all NE concentrations compared to controls. The NE-stimulated increase in gluconeogenesis above basal (0 nM NE) was also greater for trained vs control (36% vs 19%, respectively). Concomitant with the max NE-stimulated increase in gluconeogenesis, lactate uptake was significantly elevated for trained vs. control hepatocytes (307.22 ± 44.5 vs 124.5 ± 23.9 nmol/mg protein; p < 0.01), with lactate uptake quantitatively accounting for the entire increase in gluconeogenesis for trained hepatocytes. Endurance training was also observed to significantly elevate glucose production in presence of 0.6 mM palmitate, both in the absence and presence of NE. These findings confirm that hepatocytes from endurance-trained animals demonstrate enhanced rates of NE-stimulated gluconeogenesis, as well as palmitate-stimulated glucose production.